(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The issue of financial stability is linked with banking stability. Banking stability is a yardstick to determine whether an economy is sufficiently strong enough to withstand any financial challenges. Banking stability in itself relies on parameters of individual banks like liquidity risk and credit risk. The present study is an attempt to study the relation between the two risk factors with the stability of public sector commercial banks in India during the period 2009-10 to 2017-18. The study uses the simultaneous equation approach and the generalized method of moments approach for analyzing the relationship between credit and liquidity risk and their interaction on bank stability. The study shows that bank stability is significantly influenced by credit risk and liquidity risk along with growth of loans, size of bank, return on assets (RoA), and macroeconomic variables, i.e., inflation.